IN VITRO ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF GALL EXTRACTS FROM PAEDERIA PILIFERA - Sam-ang, Pornpat; Phanumartwiwath, Anuchit; Kodsueb, Rampai (Life Sciences and Environment Journal, 2020)
Maile pilain (Paederia pilifera Hook.f.) is a climbing softwood, green stem, single leaves belonging to the family Rubiaceae. It has many medicinal properties to help food digestive system, to treat fever and relief of flatulence. Some samples of P. pilifera appeared as knots are similar to tumors caused by the growth of the external tissues, particularly the young branches which is called a gall. This research was to study bioactivities of gall extracts from P. pilifera, which is new knowledge and has not been reported before, by Soxhlet extraction using hexane, dichloromethane, ethyl acetate and ethanol as solvents, respectively on antioxidant activities by DPPH and FRAP assays and determination of total phenolic contents (TPCs) by Folin-Ciocalteu method. Then, the antibacterial activity against the growth of two pathogenic bacteria, Escherichia coli and Staphylococcus aureus, was studied using the paper disc diffusion assay then further examined for determination of minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC). The result showed that the crude dichloromethane extract exhibited the relatively highest antioxidant activity with IC50 value of 2.05 mg/mL and its ferric reducing ability of 0.0397 mmol Fe2+/g extract. The crude dichloromethane extract also showed the relatively highest amount of TPCs at 81.04±0.016 mg GAE/g extract. Moreover, the crude dichloromethane extract and crude hexane extract inhibited the growth of Staphylococcus aureus with MBC values of 50 mg/mL of both crude extracts. This finding indicated that the crude dichloromethane and crude hexane gall extracts from P. pilifera have potential to be able to develop further as a herbal supplement for the therapeutic antimicrobial activities.